2013
DOI: 10.1177/1721727x1301100219
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ulcers: Treatment with Unfocused Extracorporeal Shock Waves

Abstract: The aim of this study was to evaluate the efficacy of the treatment of chronic ulcers with unfocused shock waves. Between March 2009 and February 2012 we studied a group of 124 patients, aged between 28 and 80 years, with serious wounds arisen over three months and who met the inclusion criteria for treatment. The patients were randomly divided into groups A and B, both treated with unfocused ESWT but with an average energy density for each impulse equal to 0.10 m.l/mm' in group A (total energy equal to 1.7 mJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…Saggini et al . reported significant reduction in WSA of 80% in the ESWT group treated with energy flux density of 0·1 mJ/cm 2 compared with 67% in the ESWT group treated with energy flux density of 0·04 mJ/cm 2 . A series case study reported mean reduction of WSA of 1·21 ± 0·82 cm 2 from initial wound area in four out of five patients treated with ESWT .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Saggini et al . reported significant reduction in WSA of 80% in the ESWT group treated with energy flux density of 0·1 mJ/cm 2 compared with 67% in the ESWT group treated with energy flux density of 0·04 mJ/cm 2 . A series case study reported mean reduction of WSA of 1·21 ± 0·82 cm 2 from initial wound area in four out of five patients treated with ESWT .…”
Section: Resultsmentioning
confidence: 95%
“…In the same year, Saggini et al . reported complete wound healing in 71% and partial healing in 29% of cases in the unfocused ESWT‐treated group ( n = 63), with an energy flux density of 0·01 mJ/mm 2 , compared with 40% completely healed, 37·5% improved and 22·5% unchanged in the unfocused ESWT group ( n = 40), with energy density 0·04 mJ/mm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations